Broun, Bettie. Bettie Broun to Harriet Broun, Petersburg VA, April 5, 1863 - Broun, Bettie Lee (Valdosta, GA: Valdosta State University Archives and Special Collections, 2020, 1863)
Southern Female College April 5th 1863 My Dearest Ma, I wrote you a long letter a few days ago by John Branham and have nothing of importance to write now. Nevertheless I cannot let an opportunity pass without writing a few lines to you and it's very seldom I ever have an opportunity. I hope I may receive a letter from you this morning. I dreamed last night I received so many letters from home and surely trust it may come to pass. The Yankees also trouble me very much in my dreams. They take me prisoner frequently and I am very much afraid they will take Pa or some...
Handwritten letter from Bettie Broun to her mother Harriet Broun. Southern Female College, Petersburg, Virginia [Inferred], April 5th 1863. 2 page[s].
Keywords: Personal correspondence; American Civil War (1861-1865); Virginia--Petersburg; Women's Colleges; Women College Students; Clothing and dress--Prices; Virginia--Heathsville; Letters